Pengaruh Teknik Send a Problem Terhadap Kemampuan Menulis Daftar Pustaka Siswa Kelas Xi SMA Negeri 4 Lubuklinggau - Noermanzah Noermanzah; Syaiful Abid; Epa Aprika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The objective of this research was to determine whether there is influence of the send a problem technique to the ability to write a bibliography. Influence was shown from the completeness of the results of student learning class XI SMA Negeri 4 Lubuklinggau in writing a list of libraries after applied the send a problem technique. Quantitative methods of quasi experiments are used in answering the purposes of this study. Techniques in collecting data in the form of a form of a description test technique. The research population was all students in class XI amounted to 138 students consisting of 4 classes. The sample in this research was class XI. MIA 4 which amounted to 34 students. Data analysis technique begins with the normality test, and continued with t test by looking at the difference between the KKM value which was hypothesised is 74 with the mean postes. Based on the result of test analysis with t test formula, to greater than ttable at 5 percnet significance level that is 2.60 bigger than 2.04. Thus, the results of student learning class XI SMA Negeri 4 Lubuklinggau in writing the list of libraries after applied the send a problem technique significantly completed. Keywords: Influence, Send a Problem Technique, Write Bibliography.